IMPLEMENTASI MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KARAKTER RELIGIUS PESERTA DIDIK DI SMA NEGERI 5 PALOPO - Wilda Parebangla; Mifta Zulfahmi Muassar; Sarmila Sarmila (Indonesian Journal of Islamic Studies (IJIS), 2026)
This study discusses the implementation of principal management in improving students' religious character and the factors that influence the success of the implementation of principal management in improving students' religious character. This type of research is qualitative research with data analysis using MAXQDA. Data collection techniques used are observation, interviews, and documentation. Data analysis is carried out by collecting/organizing raw data (data collection), condensing data (data condensation), presenting data (data display), drawing conclusions/verification. The results of this study indicate that (1) the implementation of the principal's management in improving the religious character of students at SMA Negeri 5 Palopo is carried out through four integrated management functions, namely: (a) Planning which is realized in the preparation of routine religious programs such as Al-Qur'an literacy (15-minute tadarus), congregational prayer, and commemoration of Islamic holidays, (b) Organization is carried out by clearly dividing tasks to religious teachers as coordinators, assisted by homeroom teachers and involving the active role of OSIS and Rohis as technical implementers, (c) Implementation is carried out by integrating the program into school activities and providing direct motivation and role models to enforce religious discipline, and (d) Supervision is carried out through checking attendance at congregational prayers and providing direct reprimands to students who are less religious. (2) Factors that influence the success of this implementation include internal factors, such as the principal's leadership commitment, teacher discipline, and the availability of facilities and infrastructure, as well as external factors that include support from parents and the community. Overall, the success of the principal's management is greatly influenced by strong collaboration between all school residents and the surrounding environment.